1992
DOI: 10.1177/026765919200700403
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postoperative normovolaemic anaemia and autotransfusion on blood saving after internal mammary artery bypass surgery

Abstract: The efficacy of two blood conservation techniques in decreasing and in preventing the use of homologous blood products was retrospectively studied in 150 patients undergoing internal mammary artery bypass surgery. Patients were matched according to prebypass blood haemoglobin (Hb) content and body surface area and were allocated to one of three groups: in the patients of group 1 (n = 50), normovolaemic anaemia (NA) was accepted postoperatively (haematocrit [Hct] was accepted to a minimum level of 25%); the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…When the blood was returned to the systemic circulation an immediate significant increase in these values was observed ( 13). Similar studies by other researchers have concluded that reinfusion of highly activated suctioned blood exacerbates wound bleeding, and they noted that high concentrations ofFDP in this blood may play a role in the observed impaired hemostasis (14,16,17,(26)(27)(28)(29)(30). In contrast, other studies have shown that an increased level of fibrinolytic activator and FDP in whole blood reinfusions has no clinically significant effect on the stimulation of systemic fibrinolytic activity.…”
Section: Reinfusion Of Whole Blood Collected From Mesothelial Spacessupporting
confidence: 61%
“…When the blood was returned to the systemic circulation an immediate significant increase in these values was observed ( 13). Similar studies by other researchers have concluded that reinfusion of highly activated suctioned blood exacerbates wound bleeding, and they noted that high concentrations ofFDP in this blood may play a role in the observed impaired hemostasis (14,16,17,(26)(27)(28)(29)(30). In contrast, other studies have shown that an increased level of fibrinolytic activator and FDP in whole blood reinfusions has no clinically significant effect on the stimulation of systemic fibrinolytic activity.…”
Section: Reinfusion Of Whole Blood Collected From Mesothelial Spacessupporting
confidence: 61%
“…Limitation of a fall in Ps0 after cardiac surgery should primarily be obtained by techniques limiting the transfusion of homologous erythrocytes [35][36][37]. In high risk patients, a fall in Ps0 could be limited by the transfusion of RBCs with a short storage time, or even of 2,3-DPGenriched blood cells [38].…”
Section: Discussionmentioning
confidence: 99%